Amped up and ready to go [broadband over power lines]. - Jones, W.D (IEEE spectrum)
Broadband over power lines, or what the Europeans prefer to call power line communications, has long been one of those just-around-the-corner technologies that holds a great deal of promise in principle but has never quite taken off. Enabling technologies on both the transmission and consumer ends have made the service easier to deliver at an attractive price. Consumers naturally would like to have broadband connections that give them more options for where they work or play. There is definitely interest in the ability to plug your notebook into an electrical socket anywhere in your home or while traveling. However, the main problem is noise. Intellon Corp., a small, fabless designer of advanced ICs based in Ocala, FL, addressed this problem while making it cheaper to implement, more secure, and easier to use. Intellon's chip sets combine orthogonal frequency division modulation, dozens of carrier channels, and automatic channel switching. This design ensures that data packets using power lines as an on-ramp to the information highway can switch lanes when they encounter problems, such as varying impedances, narrow-band interference, and impulse noise, that are inherent to that medium. To convey high-speed Internet into homes and businesses, power line communications providers must transmit their data in the form of radio signals. These signals typically have a frequency between 2 and 80 MHz, meaning they occupy the same frequency range used by hams, CB radio users, and aircraft operators. Ideally, the signals would remain confined to power lines, but because these wires are not shielded in the way coaxial cable is, they often behave like long antennas.